Animal Welfare Claims in Indonesia: Comparative Study of EU Standards and Proposed Regulatory Framework - Aprillian, R.; Leucci, F. (Tropical Animal Science Journal, 2025)
Animal welfare regulations in Indonesia have undergone recent developments, particularly with the proposed umbrella regulation for animal welfare under ministerial regulations. This development is intended to provide legal clarity and serve as a foundation for future welfare-related policies. However, a clear and harmonized animal welfare claims framework is still missing. In contrast, the European Union (EU), as a pioneer and frontrunner in animal welfare governance, has established a comprehensive standards and labelling framework. Taking from the 2009 European Commission’s animal welfare claims classification, this study aims to evaluate how Indonesia’s existing and proposed certifications related to animal welfare schemes, including Veterinary Control Number, organic, geographical indication, and halal, could be restructured to fit within a welfare claim framework. Through a comparative legal analysis, the study identifies regulatory gaps and opportunities to improve animal welfare policies in Indonesia. Particularly, the adoption of selected practices that have already been implemented in the EU could help Indonesia improve regulatory coherence, support food safety, and enhance its competitiveness in global trade.